Bushfire exposure is associated with increased pH and dark-cutting in beef longissimus thoracis at grading. (March 2023) - Hastie, Melindee; Hepworth, Graham; Hillman, Alison; Cowled, Brendan; Pfeiffer, Caitlin; Warner, Robyn D.
Abstract: To investigate if bushfire exposure is associated with increased loin pH, this study analysed temporal and geospatial data on fire incidence in South-Eastern Australia together with beef carcase quality and production records for fire affected animals ( n = 451, 299). Two outcomes were modelled: 1) loin pH at time of grading, and 2) the incidence of "high pH" defects (pH > 5.70). For both models, decreasing "time since closest fire" and "distance of property from closest fire" were associated with increasing loin pH and increased incidence of high pH carcases( p < 0.05 for all); interactions for "distance from the closest fire" with feed type (grain vs grass) and "days of fire exposure" with HGP (hormonal growth promotant) treatment (yes vs no) ( p < 0.05 for both) indicate high pH outcomes were exacerbated in grass-fed and HGP treated cattle. It is concluded that exposure to bushfire is associated with increasing pH but the extent and magnitude of these increases are modulated by production factors. Highlights: Bushfire exposure is associated with higher beef loin pH at grading. High pH outcomes are exacerbated in grass fed and hormone growth promotant treated cattle. Increasing Bos indicus content is associated with lower pH outcomes. Higher pH outcomes were associated with increasing animal age.